Substrate quality of drained organic soils—Implications for carbon dioxide fluxes. Issue 5 (26th July 2021) - Säurich, Annelie; Tiemeyer, Bärbel; Dettmann, Ullrich; Fiedler, Sabine; Don, Axel
Abstract: Background: Peatlands only cover a minor fraction of the global terrestrial surface, but due to drainage, they are major contributors to carbon dioxide (CO2 ) emissions from soils. Previous studies have shown that hydrological conditions, nutrient availability and anthropogenic disturbance play an important role in the mineralisation of organic matter. Furthermore, microbial turnover depends on peat quality, which is determined by its botanical origin and degree of transformation under natural conditions. Aims: The objective of this study was to shed light on the interdependence between mineralisation rates, secondary transformation of peat and chemical composition by examining the differences between bog and fen peat and between strongly degraded topsoil and well‐preserved subsoil. Methods: Bog and fen peat from ten different peatlands under grassland use in Germany were analysed for their chemical composition using standard 13 C nuclear magnetic resonance (NMR) spectroscopy and wet chemical extractions for fibre analysis. The radiocarbon age was determined as well. The results were combined with CO2 fluxes from a previous incubation study. Results: Topsoils had higher shares of proteins and lipids, and lower shares of carbohydrates and aromatics than subsoils. Bog peat subsoils were characterised by higher shares of carbohydrates and lower shares of aromatics than fen peat subsoils. Topsoils were more similar to each other in their chemical composition than the subsoils. Considering all samples, aromatics and phenolics were negatively correlated with CO2 fluxes. Measured CO2 fluxes from topsoils were significantly higher than from subsoils. However, no influences of chemical composition on CO2 fluxes were detected when examining topsoils and subsoils separately. Even though aromatics and phenolics showed positive relationships with radiocarbon age, differences in age alone were unable to explain the higher amounts of these compounds in the subsoil. Conclusions: The results imply that chemical composition of topsoil peat is not the reason for higher mineralisation rates compared to subsoil peat, but rather a consequence of decomposition and transformation. Thus, peat mineralisation of drained organic soils under agriculture might not slow down over time due to gradually decreasing peat quality but could increase further.